Association between gross motor function and quality of life in a group of Brazilian adults with cerebral palsy: an exploratory study - Marina Fernandes Ribeiro; Ana Paula de Mendonça; Rosane Luzia de Souza Morais (Fisioterapia e Pesquisa)
ABSTRACT International studies indicate that gross motor function can influence the health-related quality of life (HRQoL) of adults with Cerebral Palsy (CP). However, HRQoL is a complex construct that may also be influenced by cultural factors. Objective: To verify the association between Gross Motor Function (GMF) and HRQoL in a group of Brazilian adults with CP. Methods: This quantitative, cross-sectional and exploratory study included 30 individuals with CP, aged between 18 and 54 years old, living in a small/medium-sized municipality. Gross motor function was assessed using the the Gross Motor Function Classification System (GMFCS), while HRQoL was measured using the Short-Form Health Survey (SF-36), divided into physical and mental health summaries. Results: Better GMF explained 37% (adjusted R² = 0.373) of the variability in HRQoL related to functional capacity, and 22% (adjusted R² = 0.221) of the physical aspects summary. Conversely, a more compromised GMF explained 15% (adjusted R² = 0.146) of the variability in HRQoL related to emotional aspects. Conclusions: Better GMF partially explains higher HRQoL related to greater physical functioning or summary of physical aspects. On the other hand, greater impairment in GMF partially explains higher HRQoL related to emotional aspects in adults with CP residing in a Brazilian municipality. These results align with findings from international studies.